Ayurvedic Management of Rhino-Orbito-Cerebral Mucormycosis in Post COVID-19 Patient: A Single Case Study (International Journal of Ayurveda and Pharma Research, 2022)
A severe and rare fungal illness, Mucormycosis also known as black fungus affecting some corona virus patient. It occurs in people with Diabetes, Hypertension, reduced immunity and immune-compromised state. Various pharmacological interventions are used for this treatment but little efficacy and its prognosis is also poor. Certain Panchakarma procedures and internal Ayurvedic medicines have been proved to be beneficial in the management of fungal sinusitis. A 79 year old male patient with complaints of sinusitis, facial and eye pain, generalized muscular pain especially over the nape of neck, right arm, and right leg, discoloration of skin, nasal congestion came to Panchakarma OPD in university college of Ayurveda, Rajasthan Ayurveda University Campus Jodhpur for treatment. The present report deals with a case of Rhino Orbito cerebral Mucormycosis managed by Panchakarma treatment along with internal medicines. The Ayurvedic diagnoses of Raktaja Pratishyaya and Krimija Shiroroga were made, and Panchakarma treatments such as Kavala/Gandusha (gargling), Nasya (nasal medication), Dhumapana and Karnapurana were performed, followed by internal medicines for 30 days. Nasyakarma is especially desired for diseases of the parts above the base of the neck (above the clavicle). This treatment method was found effective in controlling the progressive symptoms and improving the functional ability of the patient.